Medical and scientific research in Libya. Position on sustained developmental goals - Aisha Nasef (Archives of Community Medicine and Public Health - Peertechz Publications, 2022)
UNESCO  recommendation on science and scientific researchers aims to support scientific research and science as tools for achievements of the 17 sustainable development goals (SDGs). Countries are responded differently to these recommendations. In this article we tried to assess the polices and measures taken by Libya State as a developing country to meet these recommendations. The assessment reveals big shortcomings in the Libyan government's response to UNESCO recommendation on science and scientific researchers.